2004
DOI: 10.1037/0012-1649.40.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Do You "Want" to Play? Distinguishing Between Conflicted Shyness and Social Disinterest in Early Childhood.

Abstract: This study attempted to distinguish two types of social withdrawal in early childhood: (a) one based on social fear and anxiety despite a desire to interact socially (conflicted shyness) and (b) one based on the lack of a strong motivation to engage in social interaction (social disinterest). Two samples of preschoolers (n = 119 and n = 127) 3-5 years of age participated. Their mothers completed the newly developed Child Social Preference Scale, which was designed to assess conflicted shyness and social disint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
744
6
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 577 publications
(823 citation statements)
references
References 110 publications
(189 reference statements)
47
744
6
26
Order By: Relevance
“…Contemporaneous and predictive links between parental overprotectiveness, overcontrol, and intrusion and children's socially wary and withdrawn behavior have been reported in several studies (e.g., Barber et al 1994;Coplan et al 2004;Lieb et al 2000;Mills & Rubin 1998;Rubin et al 1997Rubin et al , 2001. Taken together, these findings support earlier, classic writings pertaining to the role of parental overprotectiveness in the development of anxiety and social withdrawal (Levy 1943, Winder & Rau 1962.…”
Section: Parentingsupporting
confidence: 81%
“…Contemporaneous and predictive links between parental overprotectiveness, overcontrol, and intrusion and children's socially wary and withdrawn behavior have been reported in several studies (e.g., Barber et al 1994;Coplan et al 2004;Lieb et al 2000;Mills & Rubin 1998;Rubin et al 1997Rubin et al , 2001. Taken together, these findings support earlier, classic writings pertaining to the role of parental overprotectiveness in the development of anxiety and social withdrawal (Levy 1943, Winder & Rau 1962.…”
Section: Parentingsupporting
confidence: 81%
“…Hence, we did not compare the associations between these constructs and theoretically relevant external variables. However, other studies have suggested that these constructs have differential associations with behavioral and psychophysiological variables and familial risk for psychopathology (Coplan et al, 2004;Durbin et al, 2005;Henderson et al, 2004). Additionally, research has shown a relationship between these temperament constructs and later psychopathology, specifically depression and anxiety (Clark & Watson, 1991;Fox et al, 2005;Kagan, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the role of the BIS has been revised in more recent formulations of Gray's theory (Gray & McNaughton, 2000;McNaughton & Corr, 2004). Thus, McNaughton and Corr (2004) view the BIS as a conflict detection system associated with anxiety that modulates both the BAS in regulating approach behavior in reward-related contexts and the flight/fight system in regulating avoidance behavior in fear-eliciting contexts A number of investigators have distinguished between two groups of socially withdrawn children: a shy-conflicted, reticent group that wishes to engage in peer interactions but withdraws due to fear and anxiety; and a passive-solitary, disinterested group that withdraws due to a lack of desire for social interactions (Asendorpf, 1990;Coplan, Prakash, O'Neil, & Armer, 2004;Coplan, Rubin, Fox, Calkins, & Stewart, 1994;Harrist, Zaia, Bates, Dodge, & Pettit, 1997). Importantly, these subgroups have been shown to differ on a number of variables, including maternal reports of social fear, NA, and attention span; teacher ratings of anxiety; child ratings of perceived competence; EEG alpha power; and respiratory sinus arrhythmia (Coplan et al, 2004;Henderson, Marshall, Fox, & Rubin, 2004).…”
mentioning
confidence: 99%
“…Cependant, pour Kolligian et Sternberg (1991) (Langford et Clance, 1993). La surprotection parentale a été liée à de la timidité, à des troubles intériorisés et un lieu de contrôle externe, lui-même lié à une perception de faible compétence (Chorpita et Barlow, 1998;Coplan, Prakash, O'Neil et Armer, 2004;Rubin, Burgess et Hastings, 2003;Spokas et Heimberg, 2009). Selon Leary et al (2000), pour prévenir les situations d'échec qui pourraient menacer leur estime de soi déjà fragilisée, ces jeunes tendraient alors à dénigrer publiquement leurs performances.…”
Section: Méthode D'analyse Des Donnéesunclassified